EU Regular Economic Report 4 : Thinking CAP - Supporting Agricultural Jobs and Incomes in the EU - World Bank Group (World Bank, Washington, DC, 2018)
The European Union (EU) Regular Economic Report (RER), is an annual publication of the World Bank Group and covers economic developments, prospects, and economic policies in the European Union. The report finds that while growth is back on track, the bottom 40 percent of the income distribution is lagging behind in the EU’s recovery. This is likely caused by the interaction between involuntary increases in part-time work, technological change, a decline in the bargaining power of labor, an ageing population and weak overall productivity growth. However, absolute poverty (estimated using a poverty line defined specifically for this report) should continue to fall in Europe, driven by strong poverty reduction in central Europe. The special section of this Regular Economic Report assesses the impact of the Common Agricultural Policy on inclusive growth - past and present. The report argues that the process of structural transformation in the EU is largely on track, with the decoupled and non-market distorting components of the CAP playing a positive role in the reduction of poverty and the creation of better jobs for farmers. The gap between agricultural incomes and incomes in other sectors is also closing, while across the EU agricultural incomes are converging with each other. The successful transformers, about half of the Member States, have turned agriculture into a key sector for shared prosperity in rural areas: agriculture is no longer associated with poverty. The other half—the incomplete transformers—still have some way to go, which includes ensuring that the basic conditions for agriculture to thrive are in place: roads, advisory services, secure property rights, and access to health and education. This will ensure a more efficient use of CAP resources.